Locally projectively flatness and locally dually flatness of generalized Kropina conformal change of m-th root metric - Achal Singh; Manoj Kumar; Chayan Mishra (AUT Journal of Mathematics and Computing, 2022)
In this paper, we consider the generalized Kropina conformal change of m-th root metric and for this, prove a necessary and sufficient condition of locally projectively flatness. Also we proved a necessary and sufficient condition for the generalized Kropina conformal change of m-th root metric is locally dually flat.